Quality of Experience in Relation to Personal Informatics Tools: The Analysis and Modelling of Quality of Experience for IoT - Dong-Hee Shin (International Telecommunications Society (ITS), 2017)
The exponential growth of services via personal informatics (PI) is making it increasingly important to cater to the quality expectations of end users. Quality of experience (QoE) becomes the guiding paradigm for managing quality provisioning and application design in PI. This study examines the relationship between human experience and quality perception in relation to the IoT, developing a conceptual model for QoE in PI. By integrating human perception and experience factors involving quality and heuristics into the assessment, our study proposes a user experience model that conceptualizes a QoE specific to PI and highlights its relationship with other factors. This model establishes a foundation for future IoT service categories through a heuristic quality assessment tool from a consumer-centered perspective. The results provide a ground truth basis for developing future PI services with QoE requirements, as well as for dimensioning the underlying network-provisioning infrastructures, particularly with regard to mobile access technologies. This study provides key insights into the role of expectations and experiences in technology adoption, while supporting a quality model.
Keywords: 330; quality of experience; quality of service; user experience; personal informatics; Internet of things; quality measurement; human-centered design